(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: This study aimed to assess the prevalence of anxiety, stress, and depression and to identify its associated factors among medical students. Subject and method: A cross-sectional study was conducted among 810 medical students from November 2025 to May 2026. Data were collected using a structured questionnaire, and the Depression Anxiety Stress Scales (DASS-21) was used to assess mental health status. Statistical analyses were performed to determine the associations between selected characteristics and mental health outcomes. Results: The prevalence of anxiety, stress, and depression was 38.6%, 23.7%, and 36.2%, respectively, with most students having mild or moderate symptoms. The mean DASS-21 scores increased with the severity level, from the normal group (2.26 ± 2.17; 6.31 ± 4.02; 3.41 ± 2.82) to the extremely severe group (25.50 ± 5.37; 38.20 ± 3.35; 34.70 ± 5.44). Difficulty making new friends, conflicts with close friends, conflicts within the peer group, and frequently witnessing parental conflicts were significantly associated with anxiety, stress, and depression (p < 0.05). In contrast, having at least one close friend and regularly sharing personal problems with a trusted person were associated with lower levels of anxiety and depression. Conclusion: Mental health problems remain common among medical students. Positive social relationships and emotional support were associated with better mental health, suggesting the need for psychological support and stronger social connections in medical education.